2019
DOI: 10.1177/0961203319828519
|View full text |Cite
|
Sign up to set email alerts
|

The impact of SLE on health-related quality of life assessed with SF-36: a systemic review and meta-analysis

Abstract: Objective To evaluate the impact of systemic lupus erythematosus (SLE) on health-related quality of life (HRQoL) assessed with SF-36 and explore factors associated with HRQoL in SLE patients. Methods A random-effect meta-analysis was performed to calculate extracted data. Sensitivity and subgroup analyses were performed to distinguish sources of heterogeneity. Results A total of 36 articles were finally included in this meta-analysis, including 6510 patients. The pooled mean scores of SF-36 physical component … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
32
0
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 69 publications
1
32
0
3
Order By: Relevance
“…A large number of studies have examined the validity of the SF-36 questionnaire, showing that the physical activity subscale discriminates between various diseases and healthy controls [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. In ME/CFS patients Jason et al reported the ability of the different subscales of the SF-36 questionnaire to discriminate CFS patients from healthy controls [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies have examined the validity of the SF-36 questionnaire, showing that the physical activity subscale discriminates between various diseases and healthy controls [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. In ME/CFS patients Jason et al reported the ability of the different subscales of the SF-36 questionnaire to discriminate CFS patients from healthy controls [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…SF-36 has been certainly the most widely used and reliable to assess self-perceived health status. 7…”
Section: Discussionmentioning
confidence: 99%
“…Among these PROs, the most frequenly employed is the Medical Outcomes Study Short Form-36 (SF-36) questionnaire, able to reveal the disease impact on QoL. 7…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have revealed that SLE can exert detrimental influences on different aspects of patients’ life, leading to an impairment of psychological health (e.g., depression and low self-esteem), health-related quality of life, and sexual function. 24…”
Section: Introductionmentioning
confidence: 99%